Pediatric Concussion. - Purrier, Nicole (Optometry & Visual Performance, 2020)
Concussion is defined as a mild traumatic brain injury with symptoms typically lasting days to weeks after the initial injury. Increased concern regarding the lasting effects of a concussion has prompted researchers to critically evaluate differences in recovery, treatments, and other factors in pediatric populations. Age-specific studies of concussion are currently lacking; adult guidelines for treatment after a concussion are being applied to pediatric populations. Current research has challenged the traditional treatment of strict rest in younger individuals after a concussion, evaluated the adherence to management protocols, and assessed the financial burden of taking care of a child after a concussion. Understanding the differences between adult and pediatric populations after a brain injury is essential in determining the proper treatment for the individual. It is the goal of these article reviews to highlight research in the field of pediatric concussion today.